Repercussões da Revolução Russa na imprensa operária de São Paulo : (1917-1921) - Santos, Michel Felipe Silva Lima dos (2024)
This article aims to analyze the repercussions of the Russian revolution within the Brazilian labor movement during the years 1917 to 1921, in the state of São Paulo focusing on an important channel of opinion formation and political debate in the mid-to-early 20th century: the Brazilian Labour’s press. In this way, we intend to verify how the events of the Russian revolution were received and interpreted by these vehicles of communication and organization of the working class, as well as understanding how the revolution influenced the process of social struggle in Brazil, based on the newspapers “A Obra” (São Paulo, 1920), “A Razão” (Bauru, 1919) and “A Plebe” (São Paulo, 1917).